Progress on gait disorders, balance disorders and falls in patients with cerebral small vessel disease - Ru WANG; Nan LIU; Shao-peng WANG; Hong-yi ZHAO; Ju-mei DU; Yong-hu HUANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
Cerebral small vessel disease (cSVD) is the leading cause of chronic cerebral hypoperfusion. Gait, balance disorders and falls associated with white matter lesions can increase the risk of sickness and death in patients with cSVD. Therefore, understanding the correlations between gait, balance disorders and falls and white matter lesions, pathophysiological mechanisms, evaluation methods, etc., can help to predict the occurrence of falls and can be taken against their potential risks. Corresponding interventions can improve the quality of life of patients with cSVD.